1998
DOI: 10.1002/(sici)1521-186x(1998)19:6<384::aid-bem6>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microwaves emitted by cellular phones on human slow brain potentials

Abstract: The influence of electromagnetic fields (EMF) emitted by cellular phones on preparatory slow brain potentials (SP) was studied in two different experimental tasks: In the first, healthy male human subjects had to perform simple self‐paced finger movements to elicit a Bereitschaftspotential; in the second, they performed a complex and cognitive demanding visual monitoring task (VMT). Both tasks were performed with and without EMF exposure in counterbalanced order. Whereas subjects' performance did not differ be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(68 citation statements)
references
References 8 publications
3
62
1
2
Order By: Relevance
“…Several studies have investigated the interaction between mobile phones and brain functions in humans including their effect on hearing [9][10][11][12][13][14][15][16][17]. Some of the similar recent studies have been highlighted below:…”
Section: Discussionmentioning
confidence: 80%
“…Several studies have investigated the interaction between mobile phones and brain functions in humans including their effect on hearing [9][10][11][12][13][14][15][16][17]. Some of the similar recent studies have been highlighted below:…”
Section: Discussionmentioning
confidence: 80%
“…Some of the studies indicated that EMF caused a reduction in the voltage of slow potentials. However, a more detailed analysis of the results and their verification in further experiments did not confirm the earlier observations [12][13][14]. Considering the limitations of the EEG method, in our current work we decided to use determinations of P300 wave to assess EMF effect on auditory cortex ERPs.…”
Section: Discussionmentioning
confidence: 99%
“…As the induced brain activity in higher frequency bands has been proposed to be a correlate of coherent high frequency neuronal activity, PEMF exposure may provide a means to systematically alter the pattern fluctuations in neural mass activity. Freude et al [1998] found a significant effect on slow brain potentials at central and temporo-parietooccipital regions during exposure to cell phone emissions. The influence of EMF emitted by a cellular phone positioned at the left ear, on preparatory slow brain potentials (SP) was studied in two different tasks: in the first, healthy male human subjects had to perform simple self-paced finger movements to elicit a Bereitschaftspotential (BP); in the second, they performed a complex and cognitive demanding visual monitoring task (VMT).…”
Section: Electroencephalography and Evoked Responsesmentioning
confidence: 98%